2008
DOI: 10.1007/s00586-008-0799-2
|View full text |Cite
|
Sign up to set email alerts
|

Posterior lumbar interbody fusion using rhBMP-2

Abstract: The use of biological technologies for the treatment of degenerative spinal diseases has undergone rapid clinical and scientific development. BMP strategies have gained wide support for an inherent potential to improve the ossification process. It has been extensively studied in combination with various techniques for spinal stabilisation from both anterior and posterior approach. We studied the fusion process after implantation of rhBMP-2 in 17 patients with degenerative lumbar spine diseases in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 14 publications
1
38
1
1
Order By: Relevance
“…Vertebral and nonvertebral bone resorption 41,48,55,60,61,156,[164][165][166][167][168][169][170] Graft subsidence 41,60,61,166,171 Urogenital events Retrograde ejaculation 76,[172][173][174][175] Bladder retention 172,175 Wound complications Hematoma No competing financial interests exist.…”
mentioning
confidence: 99%
“…Vertebral and nonvertebral bone resorption 41,48,55,60,61,156,[164][165][166][167][168][169][170] Graft subsidence 41,60,61,166,171 Urogenital events Retrograde ejaculation 76,[172][173][174][175] Bladder retention 172,175 Wound complications Hematoma No competing financial interests exist.…”
mentioning
confidence: 99%
“…Bone resorption, osteolysis and implant displacement were observed [49,50]. Other authors reported bone overgrowth into the spinal canal in PLIF and radiculitis, osteolysis and loss of alignment [46,49,[51][52][53].…”
Section: Graftmentioning
confidence: 85%
“…6 Vaidya et al further noted that abdominal contents precluded adequate radiographic visualization in nine patients, and in their author reply, that ''It is our belief that endplate resorption occurs in all patients that undergo rhBMP assisted spinal fusion". 7 Vaidya's belief was confirmed by Meisel et al 8 In 2007 surgeons from Thomas Jefferson reported on 68 TLIF procedures; rhBMP-2 was implanted in 39 of the patients. 9 Patients receiving BMP-2 were eight times more likely to report postoperative radicular pain.…”
mentioning
confidence: 75%